تحسين جودة خدمات النقل الداخلي من منظور مدخل إدارة الجودة الشاملة دراسة تطبيقية على الشركات العامة للنقل الداخلي في سورية - زاهر بسام (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتمثل الهدف من البحث في تقويم كفاءة وفعالية جودة خدمات شركات النقل الداخلي من منظور إدارة الجودة الشاملة، وقد تضمن التقويم الجوانب الآتية: - رضاء العملاء عن جودة خدمات النقل الداخلي. - الأساليب العلمية لتحسين جودة خدمات النقل الداخلي. - الثقافة التنظيمية السائدة. - أنشطة الصحة والسلامة المهنية ومنع الحوادث. وقد أشار البحث إلى التوصيات الآتية: - العمل على تحقيق رضاء العملاء عن خدمات النقل الداخلي من حيث: أماكن جلوس مريحة، سرعة الوصول إلى المكان المقصود، فترة انتظار قليلة، تغطية خطوط النقل الداخلي للمناطق كافة. - العمل على استبدال الباصات المتقادمة بباصات حديثة متوسطة الحجم. - التركيز على الصيانة الوقائية. - التوافق مع متطلبات الأيزو 9001 إصدار عام 2000. - التوافق مع متطلبات الأيزو 14001. - توافر ثقافة تنظيمية إيجابية مساعدة على تحسين جودة خدمات النقل الداخلي. - القيام بمجموعة من الأنشطة لضمان الصحة والسلامة المهنية ومنع الحوادث. - التوعية والتخطيط لتطبيق مدخل إدارة الجودة الشاملة. - القيام بمجموعة من الإجراءات لتطبيق مدخل إدارة الجودة الشاملة. The main purpose of this research is to evaluate the efficiency and effectiveness of the quality of services of internal transport companies in Syria from a total quality management perspective. The following aspects are evaluated: Customers’ satisfaction of the quality of internal transport services. Use of scientific methods to improve the quality of services. Prevailing organizational culture. Vocational safety, health, and accident prevention activities. The research offers the following recommendations: Work to fulfil the customers satisfaction of internal transport services, comfortable sitting places, arrival speed destination, covering internal transport lines to all regions. Work to replace obsolete buses with modern medium-size buses. Emphasis on preventive maintenance. Accordance with ISO 9001: 2000 requirements. Accordance with ISO 14001 requirements. Spreading a positive organizational culture that helps to improve the quality of internal transport services. Making sure that vocational safety, health, accident prevention activities are conducted. Raising awareness and planning to implement total quality management approach. Following a group of procedures to implement total quality management approach.